Methyl parathion : Environmental health criteria 145 - Hertel, R. F (WHO, 1993)
Evaluates the risks to human health and the environment posed by methyl parathion, a highly toxic organophosphorus ester insecticide. Introduced as a commercial chemical in 1949, methyl parathion is used as a contact insecticide and acaricide for the protection of cotton, soybeans, cereals, tobacco, peanuts, vegetables, citrus fruits, and other crops. The compound is applied as a foliar spray by aircraft or ground equipment.
Environmental Health Criteria ; 145
Keywords: Methyl Parathion; chemie, klinická chemie; vystavení vlivu životního prostředí; methylparathion; Environmental Exposure; environmentální vědy